Complete mitochondrial genome of Red bigeye (Priacanthus macracanthus): genome characterization and phylogenetic analysis - Sun, Yuena (Mitochondrial DNA B Resour, 2018)
Red bigeye, Priacanthus macracanthus, a species in the family Priacanthidae was added to the seafood red list by Greenpeace International due to the decline in its abundance and overfishing. To understand the phylogenetic relationship of Red bigeye in teleost, we determined the complete mitochondrial genome of Red bigeye. The complete mitochondrial genome is 17,003bp in length, including 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and 2 main non-coding regions. Phylogenetic tree shows that Red bigeye is clustered with the fishes of the order Perciformes.